Effectiveness of Siddha Topical Applications for Chronic Non-Healing Lower Extremity Ulcers- Case Series (Indian Journal of Case Reports, 2019)
A chronic ulcer is that, which does not heal within three months. Diabetic, arterial and venous ulcers are the common cause for non-healing lower extremity ulcers. The prevalence of chronic leg ulcers is 0.6-3% in people over 60 years and 5% in those over 80 years. Here, we report a case series of 6 patients with chronic non-healing ulcers. All the 6 patients received topical application of Siddha medicine. ‘Leg Ulcer Measurement Tool (LUMT)’ scoring system was used to assess the severity, prognosis and for follow-up treatment. After the 6 weeks of treatment, 33% (n=2) have ulcer size more than 5cm, 16% (n=1) have exudate in their ulcers, none of them have necrotic tissues, leg edema and peri-ulcer affected skin in their ulcers. It was found that the patients treated with Siddha medicine have satisfactory improvement in the non-healing lower extremity ulcers.